Concept of Suicide: Neurophysiological/Genetic Theories and Possible Oxytocin Relevance - Padurariu, M.; Prepelita, R.; Ciobica, A.; Dobrin, R.; Timofte, D.; Stefanescu, C.; Chirita, R. (Нейрофизиология, 2016)
The suicidal behavior is regarded as the act by which a person seeks to take his life, being aware
of the consequences of his action. In our review, besides describing the main introductory
aspects for the concept of suicide, we focus our attention on the main neurophysiological
and genetical mechanisms relevant for this extremely difficult to manage and controversial
behavior. Moreover, considering the latest interests in the current literature on the relevance
of central oxytocin to various superior cognitive behaviors, we will also make a short
description on how important effects of oxytocin could be in the context of suicidal behavior. Суїцидальна поведінка – це дії, в результаті яких особа намагається позбавити себе життя, усвідомлюючи наслідки
таких дій. У даному огляді, окрім опису основних загальних аспектів концепції суїциду, ми концентрували увагу на
основних нейрофізіологічних та генетичних аспектах, котрі
мають відношення до цього вкрай важко контрольованого та
повного протиріч типу поведінки. Окрім того, враховуючи
велику цікавість, яку викликає в сучасній літературі задіяність центральної окситоцинової системи в контроль когнітивної поведінки вищих типів, ми надали короткий опис
того, наскільки ефекти окситоцину можуть бути важливими
в контексті суїцидальної поведінки.